Gambling, housing conditions, community contexts and child health in remote indigenous communities in the Northern Territory, Australia - Stevens Matthew; Bailie Ross (BMC, 2012)
Abstract Background Recent government reports have identified gambling, along with alcohol abuse, drug abuse and pornography, as contributing to child neglect and abuse in Indigenous communities in the Northern Territory (NT). These reports also identify gaps in empirical evidence upon which to base sound policy. To address this shortfall, data from ten remote Indigenous communities was analysed to determine the relationship between gambling problems, housing conditions, community contexts and child health in indigenous communities. Methods Logistic regression was used to assess associations between gambling problems, community contexts, housing conditions and child health. Separate multivariable models were developed for carer reported gambling problems in houses and six child health outcomes. Results Carer reported gambling problems in households across the ten communities ranged from 10% to 74%. Inland tropical communities had the highest level of reported gambling problems. Less access to a doctor in the community showed evidence of a multivariable adjusted association with gambling problems in houses. No housing variables showed evidence for a multivariable association with reported gambling problems. There was evidence for gambling problems having a multivariable adjusted association with carer report of scabies and ear infection in children. Conclusions The analyses provide evidence that gambling is a significant problem in Indigenous communities and that gambling problems in households is related to poor child health outcomes. A comprehensive (prevention, treatment, regulation and education) public health approach to harm minimisation associated with gambling amongst the Indigenous population is required that builds on current normative community regulation of gambling.